TMOD-16. A NOVEL ADENOVIRAL-PERMISSIVE, IMMUNOCOMPETENT HAMSTER GLIOMA MODEL TO EVALUATE ONCOLYTIC ADENOVIRAL THERAPY. (9th November 2020) - Phillips, Lynette; Gumin, Joy; Li, Shoudong; Daou, Marc; Ledbetter, Daniel; Hossain, Anwar; Kerrigan, Brittany Parker; Gomez-Manzano, Candelaria; Fueyo, Juan; Lang, Frederick
Abstract: Oncolytic adenoviruses, including Delta-24-RGD, target tumors by direct tumor cell oncolysis and by activation of an anti-tumor immune response. Due to the species selectivity of oncolytic adenoviruses, there is currently no single preclinical animal model of glioma that supports viral replication, tumor oncolysis, and virus-mediated immune responses. To address this gap, we took advantage of the Syrian hamster to develop the first glioma model that is both adenovirus replication-permissive and immunocompetent. Hamster glioma stem-like cells (GSCs), transformed by forced expression of hTERT, SV40 large T antigen, and h-RasV12, reproducibly form intracranial tumors in hamsters. In vitro, electron microscopy and cytopathic effect assays demonstrated that hamster GSCs supported viral replication and were susceptible to Delta-24-RGD-mediated cell death. In vivo, hamster GSCs consistently developed into highly proliferative tumors resembling high-grade gliomas. Following intratumoral delivery of Delta-24-RGD, immunohistochemistry for viral proteins demonstrated viral infectivity and replication in hamster gliomas. Flow cytometry revealed increased T cell infiltration in Delta-24-RGD-infected tumors. Delta-24-RGD treatment of tumor-bearing hamsters led to significantly increased survival compared with hamsters treated with PBS. Using this model, we evaluated the effects of corticosteroid-mediated immunosuppression on Delta-24-RGD efficacy. Dexamethasone treatment significantly decreased peripheral blood lymphocytes, decreased tumor-infiltrating lymphocytes, and suppressed the levels of serum anti-adenovirus antibodies. Dexamethasone reduced the number of long-term survivors and decreased the median survival (50 days for Delta-24-RGD + dexamethasone vs undetermined for Delta-24-RGD alone). In summary, we have developed the first adenovirus-permissive, immunocompetent hamster glioma model, addressing a critical need for a model in which to study the role of direct oncolysis in driving immune mediated viral clearance versus driving an antiglioma immune response. Understanding these mechanisms is critical to optimizing the success of oncolytic adenoviral therapy in the clinic.